A agroecologia e a etnobotânica: aspectos multidimensionais da pesquisa nos agroecossistemas - Vasconcelos, Paulo Henrique de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Agroecology deals with studies about open systems that are susceptible to high rates of intrinsic and extrinsic variations, resulting in multidimensional proportions of its characteristics. These systems, composed by an ecosystem and an agricultural matrix, named agroecosystems have as a principle under an agroecological perspective the utilization of agronomic scientific knowledge allied to the maintenance of the relationships between human beings and environment. The ecological dimension is one of the most important in Agroecology, in it resides the intention of utilizing practices that will minimally interfere with the environment, affecting in a bland way the trophic chains that cohabits with the farmer's worker place. Generally, even if the human being interacts and acts directly in the transformation of the environment to a tillage, he should also worry in realizing actions that promote environmental conservation of his working and housing place on the countryside. To understand these relations and maintain conservation methods is necessary a comprehension that evaluate the possible different interactions that could occur in the agroecosystems, in other words, is necessary a multidimensional view. The agroecosystems, in a biological perspective, includes studies not only about the biological and ecological relations of growing plants but also of its evolutionary relationship with the human species, in an Ethnobotany related knowledge. In these studies are considered, for example, evolutionary aspects involving culture transmission and its importance for the maintenance of practices in agriculture; direct relations between human beings and the environment, resulting in particular ecological relations; and even more sustainable approaches such as ecological relations between growing plants and any other organisms and abiotic components. Appropriating of studies that can identify these factors in...

A Agroecologia trata do estudo de sistemas abertos que, por sua vez, estão susceptíveis a altas taxas de variações intrínsecas e extrínsecas, culminando em proporções multidimensionais de suas características. Estes sistemas compostos por um ecossistema e uma matriz agrícola são denominados agroecossistemas e possuem como princípio, sob a perspectiva da Agroecologia, a utilização do conhecimento científico agronômico aliado à manutenção das relações entre o ser humano e o ambiente. Dentre as mais importantes dimensões da Agroecologia destaca-se a ecológica, onde há o intuito em utilizar práticas que pouco irão interferir no meio ambiente, impactando da maneira mais branda possível as cadeias tróficas existentes na localidade de trabalho do agricultor. De maneira geral, mesmo que o ser humano interaja e atue diretamente na transformação do ambiente para o cultivo, deve também preocupar-se em realizar ações que promovam a conservação ambiental de seu local de trabalho e de moradia no campo. Para o entendimento destas relações e manutenção de métodos de conservação, é necessária uma compreensão que avalie as diferentes interações passíveis de ocorrência nos agroecossistemas, ou seja, é necessária uma abordagem multidimensional. Os agroecossistemas, dentro de uma perspectiva biológica, compreendem estudos não só sobre a biologia de plantas de cultivo e de suas relações ecológicas, mas podem também tratar das relações evolutivas da espécie humana com as espécies vegetais no conhecimento relacionado com a Etnobotânica. São levados em consideração nestes estudos, por exemplo, aspectos evolutivos acerca da transmissão de cultura e sua importância para a manutenção de práticas na agricultura; relações diretas entre o homem e o ambiente natural, configurando relações ecológicas particulares; e até mesmo abordagens mais sustentáveis, como...
Keywords: Ecologia agrícola; Agrobiodiversidade; Etnobotânica; Biodiversidade - Conservação; Sustentabilidade; Agricultural ecology